From Research to Pedagogy: Proposals to Promote Metapragmatic Awareness and Intercultural Competence in the Teaching of Italian L2 to Brazilian Learners - Porcellato, Adriana Mendes; Spadotto, Luciane do Nascimento; Silva Neto, Mayara da (Revista de Italianística, 2022)
Considering that pragmatic competence is about being able to make the most appropriate choice for a specific context, selecting one from the different options available (NUZZO; GAUCI, 2012), then teaching pragmatics should make learners notice the influence of social norms on language choices. Since social norms are linked to the L2/FL culture, it is desirable that pragmatic aspects be presented from a cross-cultural perspective, stimulating learners to reflect on social and linguistic conventions in the L1 and L2/FL (LIDDICOAT; SCARINO, 2013), thus promoting the development of metapragmatic awareness (McCONACHY, 2013). Here we present a set of pedagogical activities developed from the data collected and analyzed by the Grupo de Pesquisa em Pragmática (Inter)linguística, Cross-cultural and Intercultural at the University of São Paulo. In such activities, students are led to compare the realizations of the linguistic act of request in Italian and Brazilian Portuguese with the aim of promoting a reflection on how contextual variables (such as social distance and degree of imposition) may have different effects on Italians’ and Brazilians’ linguistic choices. The teaching activities described here, therefore, are aimed at developing both metapragmatic awareness and learners’ intercultural competence.